The FLOODLABEL as a social innovation in flood risk management to increase homeowners' resilience - Meyer, Helene; Hartmann, Thomas (Technische Universität Dortmund, 2023)
In flood risk management awareness has been growing that the responsibility for coping with a flood cannot be assumed by the government alone. Homeowners need to be actively involved in flood risk management by taking responsibility; for this, they need empowerment and support to take adequate precautions. If homeowners implement precautionary measures, they can mitigate damage caused by floods and thus increase their resilience. This requires an appropriate risk communication strategy with the population. The FLOODLABEL in Germany informs and prompts homeowners to take precautionary measures. The Flood Competence Center developed the FLOODLABEL. This study employs the analytical framework of social innovation as the FLOODLABEL has some characteristics of social innovation. This study first explores the FLOODLABEL, which constitutes social innovation in flood risk management, and therefore characterizes the five development phases and their successes and challenges as social innovation. Second, it tries to understand and reflect upon the current stage of the FLOODLABEL as a social innovation in Germany and seeks to learn from this tool about the potential drivers associated with the process of implementation. Third, there is potential to gather a better understanding of other social innovations in flood risk management.
Journal of flood risk management;
Keywords: flood prevention; flood risk management; resilience; self-precaution; social innovation; 710